Sustainable Futures as Problems of Social Order: Editorial Introduction - Bazzani, Giacomo; Maurer, Andrea; Siri, Jasmin (Zeitschrift für Theoretische Soziologie, 2026)
Sustainability has become a general horizon of political legitimacy, economic justification and moral evaluation, yet its sociological significance remains insufficiently specified. This Special Issue argues that sustainability should be treated not as a specialized environmental topic, nor as a managerial language of policy adjustment, but as a problem of social order under ecological constraint. Recent scholarship have shown that sustainability is contested, future-oriented, institutionally mediated and normatively charged. The contribution of this special issue lies in conceptualizing sustainability by emphasizing four dimensions usually analyzed separately: Solidarity, collective action, money and imagination. The articles combine theoretical concepts with empirical case studies and demonstrate how sustainability can be theoretically conceptualized in sociology. Sustainable futures, we argue, are struggles over who counts, how common goals are reached, what is institutionally valued and which futures become credible enough to organize present action. This framework reconnects theory, empirical inquiry and reflexive normativity.